Gábor Ittzés and Miklós Péti, eds. Milton Through the Centuries. Budapest: Károli Gáspár U of the Reformed Church in Hungary and L’Harmattan, 2012. 337 pages. - Najbauer, Noémi (FOCUS: Papers in English Literary and Cultural Studies, 2014)
The eponymous collection of the conference proceedings appeared in 2012. Its editors, both contributors themselves, view the volume as “represent[ing] a rough cross-section of the diversity of approaches at the … conference” (ix) with an admitted focus on Milton’s poetic oeuvre and its reception over the centuries. The title of the volume serves also as its organizing principle, as the papers are divided into two categories under the headings of “Milton” and “Through the Centuries” respectively. It is here that my single contention lies. Namely, the two somewhat vaguely titled units could have been further subdivided to better show the connections between the papers and highlight the most prevalent scholarly trends.